Electrografting of 4-Nitrobenzenediazonium Salts on Al-7075 Alloy Surfaces—The Role of Intermetallic Particles - Jiangling Su; Juan Carlos Calderón Gómez; Guido Grundmeier; Alejandro González Orive (Nanomaterials, 2021)
In this work, the electrografting of Al-7075 aluminium alloy substrates with 4-nitrobenzenediazonium salt (4-NBD) films was studied on a complex aluminium alloy surface. Prior to the electrografting reaction, the substrates were submitted to different surface treatments to modify the native aluminium oxide layer and unveil intermetallic particles (IMPs). The formation of the 4-NBD films could be correlated with the passive film state and the distribution of IMPs. The corresponding electrografting reaction was performed by cyclic voltammetry which allowed the simultaneous analysis of the redox reaction by a number of complementary surface-analytical techniques. Spatially resolved thin film analysis was performed by means of SEM-EDX, AFM, PM-IRRAS, Raman spectroscopy, XPS, and SKPFM. The collected data show that the 4-NBD film is preferentially formed either on the Al oxide layer or the IMP surface depending on the applied potential range. Potentials between −0.1 and −1.0 VAg/AgCl mostly generated nitrophenylene films on the oxide covered aluminium, while grafting between −0.1 and −0.4 VAg/AgCl favours the growth of these films on IMPs.